Cost management for university libraries : - Ceynowa, Klaus (K.G. Saur, 2003)
The cost accounting guidelines of this volume were developed through a project sponsored by the university libraries in Munster and Paderborn, Germany. The cost accounting methods were conceived as part of the fiscal framework of the main service institutions at universities. Methods for forecasting